Effects of temperature and PAR on the photosynthesis of Kappaphycus sp. (Solieriaceae, Rhodophyta) from Okinawa, Japan, at the northern limit of native Kappaphycus distribution in the western Pacific. Issue 4 (1st July 2017) - Borlongan, Iris Ann; Nishihara, Gregory N.; Shimada, Satoshi; Terada, Ryuta
Abstract: The successful cultivation of the Japanese Kappaphycus sp. ( K. striatus auctorum japonicorum) in Okinawa, Japan, requires the detailed understanding of its physiological response to environmental factors. The photosynthetic performance of this native red alga was investigated under a variety of temperature and photosynthetic active radiation (PAR) conditions by employing methods based on pulse amplitude modulation–chlorophyll fluorometry and dissolved oxygen sensors. The net photosynthesis–irradiance ( P–E ) curve at 24°C revealed that the compensation ( Ec ) and saturation ( Ek ) irradiances were 26 [95% Bayesian prediction interval (BPI), 11–29 μmol photons m −2 s −1 ] and 140 (95% BPI, 98–192) μmol photons m −2 s −1, respectively. No inhibition in oxygenic evolution and quantum yield was observed at the highest PAR of 1000 μmol photons m −2 s −1 . However, the ability of the seaweed to recover from photoinhibition was complicated following long-term PAR exposures at 18°C but not at 28°C. The Japanese Kappaphycus sp. showed photosynthetic optima at 17.4–29.1°C, derived from the Fv / Fm and gross photosynthesis–temperature models, respectively. These characteristic results were closely related to the depth of its habitat and its northern limit of distribution in Okinawa as influenced primarily by seawater temperature. Findings of this study should be useful to the development of culture systems adapted for subtropical waters, whether for commercial purpose or for conservation of natural communities.